'Teaching from the Heart': challenges for non-Aboriginal teachers teaching Stage 6 Aboriginal Studies in NSW secondary schools. Issue 2 (5th December 2021) - Stern, Daniel; Burgess, Cathie
Abstract: This paper explores the unique challenges, experiences and circumstances that enable and/or constrain non-Aboriginal teachers involved in teaching the Stage 6 Aboriginal Studies syllabus in the New South Wales (NSW) curriculum (2010). Drawing on the yarning inquiry methodology of Bessarab and Ng'andu, seven semi-structured interviews were conducted with Aboriginal and non-Aboriginal Aboriginal Studies teachers to open a powerful and insightful dialogue pertaining to the complexities and challenges for non-Aboriginal teachers teaching in the Aboriginal Studies space. Interview data identified key issues, strategies and themes relating to how non-Aboriginal teachers of Aboriginal Studies negotiate and operate in highly contested knowledge spaces, their roles and responsibilities as social justice educators and their capacity to enact substantive change within and beyond the Aboriginal Studies classroom. Nakata's cultural interface theory provides a useful tool for data analysis as Aboriginal Studies sits squarely at the centre of this interface. The findings provide valuable insights and practical recommendations for aspiring and current non-Aboriginal Aboriginal Studies teachers seeking to develop a clearer understanding of their, thus far under-researched, roles within the classroom, whilst opening an intriguing dialogue pertaining to the future of Aboriginal Studies in schools and its place within Australia's broader movement for conciliation.